The Impact of Economic Openness on Indonesian Spice Exports to The United States: Gravity Model Approach - Herdiana Anggrasari; Aura Dhamira (Westscience Press, 2026)
The existence of a free market increases the level of competition between countries because non-tariff barriers are reduced. This phenomenon is a serious concern amidst the issue of liberalization and international economic integration because each country has the same interest in gaining maximum benefit from open market access. This study uses a modified or developed gravity equation model (extended gravity model) to analyze the effect of economic openness on the flow of Indonesian spice export trade to the United States. This study reveals how the openness of the United States economy significantly affects the flow of Indonesian spice trade, both in the short and long term. With the strengthening of bilateral relations between the two countries, Indonesia has the opportunity to optimize spice exports and facilitate trade negotiations in the international market.